![Ex 4.1, 10 - Chapter 4 Class 11 Mathematical Induction - Part 2](https://cdn.teachoo.com/35d530ec-1720-4bf2-bdcf-38858a513e57slide26.jpg)
![Ex 4.1, 10 - Chapter 4 Class 11 Mathematical Induction - Part 3](https://cdn.teachoo.com/8df3d302-3401-47de-986e-b6a26649d300slide27.jpg)
![Ex 4.1, 10 - Chapter 4 Class 11 Mathematical Induction - Part 4](https://cdn.teachoo.com/453f26cb-0ad3-4fe4-aaca-e8f3a3bfc555slide28.jpg)
Equal - 1 upon addition
Last updated at Dec. 16, 2024 by Teachoo
Question10 Prove the following by using the principle of mathematical induction for all n N: 1/2.5 + 1/5.8 + 1/8.11 + .+ 1/((3 1)(3 + 2)) = /((6 + 4)) Let P (n) : 1/2.5 + 1/5.8 + 1/8.11 + .+ 1/((3 1)(3 + 2)) = /((6 + 4)) For n = 1, L.H.S = 1/2.5 = 1/10 R.H.S = 1/((6(1) + 4)) = 1/((6 + 4)) = 1/10 Hence, L.H.S. = R.H.S , P(n) is true for n = 1 Assume P(k) is true 1/2.5 + 1/5.8 + 1/8.11 + .+ 1/((3 1)(3 + 2)) = /((6 + 4)) We will prove that P(k + 1) is true. R.H.S = (( + 1))/((6( + 1) + 4) ) L.H.S = 1/2.5 + 1/5.8 + 1/8.11 + .+ 1/((3( +1) 1)(3( +1)+ 2))